Short Antibiotic Treatment Duration for Osteomyelitis Complicating Pressure Ulcers: A Quasi-experimental Study. (16th February 2023) - Dinh, Aurélien; D'anglejan, Emma; Leliepvre, Helene; Bouchand, Frédérique; Marmouset, Damien; Dournon, Nathalie; Mascitti, Hélène; Genet, François; Herrmann, Jean-Louis; Chaussard, Haude; Duran, Clara; Noussair, Latifa
Abstract: Background: Osteomyelitis-complicating pressure ulcers are frequent among patients with spinal cord injuries (SCIs), and the optimal management is unknown. In our referral center, the current management is debridement and flap coverage surgeries, followed by a short antibiotic treatment. We aimed to evaluate patients' outcomes a year after surgery. Methods: We performed a quasi-experimental retrospective before/after study on SCI patients with presumed osteomyelitis associated with perineal pressure ulcers. We included all patients who underwent surgery with debridement and flap covering, followed by effective antibiotic treatment, between May 1, 2016, and October 30, 2020. The effective antimicrobial treatment duration included the 10 days leading up to January 1, 2018 (before period), and the 5 to 7 days after (after period). We also compared the efficacy of 5–7-day vs 10-day antibiotic treatment and performed uni- and multivariable analyses to identify factors associated with failure. Results: Overall, 415 patients were included (77.6% male patients; mean age ± SD, 53.0 ± 14.4 years). Multidrug-resistant organisms (MDROs) were involved in 20.7% of cases. Favorable outcomes were recorded in 69.2% of cases: 117/179 (65.3%) in the 10-day treatment group vs 169/287 (71.9%) in the 5–7-day treatment group ( P = .153). The only factor associated with failure in the multivariate analysis was a positive culture from suction drainage (odds ratio, 1.622; 95% CI, 1.005–2.617; P = .046). Effective treatment duration >7 days and intraoperative samples negative for MDROs were not associated with better outcomes ( P = .153 and P = .241, respectively). Conclusions: A treatment strategy combining surgical debridement and flap covering, followed by 5 to 7 days of effective antibiotic treatment seems safe.